Improved modulation for three-phase series-end winding voltage-source inverters - Chen, Zhi (2025)
To extend the speed range and reduce power electronics devices of the open-end winding permanent magnet synchronous machine (OEW-PMSM) drive system,series-end winding topology is adopted in this article. A simplified modulation strategy is proposed. Compared with space vector pulse width modulation (SVPWM),the proposed modulation calculates the four bridges' duty cycles in the ABC reference frame. It avoids complex sector identification and voltage vector distribution calculation,and controller design can be simplified. The asymmetry of the series-end winding topology results in asymmetric three-phase dead-time voltage errors. The characteristics of dead-time is analyzed,and a novel dead-time compensation strategy is proposed to eliminate current harmonics. Adaline neural network (ANN) algorithm is applied for harmonic extraction and serves as phase shifting generator,and closed-loop control of one-dimensional zero-sequence harmonics can be realized in rotating reference frames. Simulations and experimental results verify the effectiveness of the proposed modulation and dead-time compensation method.